Abundance Analyses of the New R Coronae Borealis Stars ASAS-RCB-8 and ASAS-RCB-10. (24th August 2017) - Hema, B. P.; Pandey, Gajendra; Kamath, Devika; Rao, N. Kameswara; Lambert, David; Woolf, Vincent M.
Abstract: Abundance analyses of the two newly discovered R Coronae Borealis (RCB) stars ASAS-RCB-8 and ASAS-RCB-10 were conducted using high-resolution optical spectra and model atmospheres. Their chemical compositions place the pair among the majority class of RCBs. ASAS-RCB-10 is one of the most N-poor majority RCBs with an above average O abundance. Relative to ASAS-RCB-10, ASAS-RCB-8 is H poor by 1.6 dex, O-poor by 0.7 dex but N-rich by 0.8 dex suggesting a higher contamination by CNO-cycled material.